Application of LKS Vision of Science, Environment, Technology, and Society in Learning Science to Improve Students’ Science Literacy of MTs - Salisah, Hajjah Yuliani; Sudarmin, Sudarmin; Wardani, Sri (Journal of Innovative Science Education, 2019)
The involvement of science, environment, society, and technology or SETS (Science, Environment, Technology, and Society) in learning makes learning more meaningful. The fluency and success in learning can be supported by the availability of more varied learning facilities, one of them with Student Worksheets (LKS). SETS visionary worksheets as a learning tool that will be developed to train students' scientific literacy in accordance with the learning material. The purpose of this study is to describe the improvement of students' scientific literacy skills between the experimental class and the control class.This study uses Nonequivalent Control Group Design. Scientific literacy skills are measured by a description of 10 items. The results showed that there were differences in the increase in scientific literacy skills between the experimental class and the control class in the low improvement category, but there was a significant difference in both quality/statistics. The percentage increase in the experimental class (41.5%) was greater than the control class (24.7%). Students' responses to the worksheets applied were very good. The conclusions in this study are that SETS vision worksheets applied can improve students' scientific literacy.